An Unenclosed Quasi-Static Cavity Resonator-Based Ubiquitous 3-D Wireless Power Transfer System Supporting Simultaneous Through-Wall Wireless Communications - Qiaoli Zhang; Lingao Fan; Fangcheng Ren; Zhen Yue; Deshuang Zhao; Shuai Ding; Bingzhong Wang (Micromachines)
With the emergence of the Internet of Things (IoT), the demand on the wireless power supply to consumer electronics simultaneously requires much more location freedom, ease of use, and performance with wireless communications. In this paper, an unenclosed quasi-static cavity resonator (QSCR) constructed with metallic strips and the design method are proposed and theoretically analyzed. This unenclosed QSCR has a simple structure, which benefits the wireless charging for portable/wearable electronics and smart appliances in the office and home environment. Meanwhile, it can achieve simultaneous ubiquitous 3-dimensional (3-D) wireless power transfer (WPT) inside the cavity and through-wall wireless communications with external electronic devices. Simulation and experimentation are performed to verify the theoretical analysis of the proposed cavity resonator and the WPT system based on it. As demonstrated, at a powering frequency of 6.78 MHz, the unenclosed QSCR can wirelessly transfer power to the receivers with a maximum power transfer efficiency of 90.5%, and an efficiency exceeding 51.5% is obtained at almost any position within the cavity space. The measured through-wall wireless communication channel attenuation introduced by the unenclosed QSCR is below 2.87 dB. By adjusting the inserted lumped capacitor value, the system can work at any desired frequency.